A phyto-pharmacological overview on Jewel Weed - Khyati Narendrakumar Shah, Preeti Verma, Bhanubhai Suhagia (Journal of Applied Pharmaceutical Science, 2017)
Jewel weed is a common name of Impatiens balsamina Linn. (Family, Balsaminaceae). It is often grown as garden plant due to its attractive foliage and flowers. It is traditionally used as diuretic, emetic, laxative, demulcent and tonic. It is reported to possess beneficial effects in lumbago, intercostal neuralgia and in burns. Studies have revealed presence of various phytoconstituents like flavanoids, triterpenoids, glycosides, fatty acids and alkaloids. The present review is an attempt to summarize traditional values, pharmacognostical and phytopharmacological reports of Jewel weed.
Keywords: Jewel weed, Impatiens balsamina, Balsaminaceae, Garden plant, phytochemical constituents.